Factors affecting medical tourists’ perception of social media platforms in hospitals in Malaysia - Balouchi, Mina (2021)
Over the years, medical tourism has gained popularity in Malaysia, and it is now a wellrecognized industry. Nonetheless, Malaysian medical tourism hospitals’ performance in terms of patient numbers and market value has been marginal when compared to its main competitors in the industry. To gain a better understanding of medical tourists’ behaviour and shed light on the practical side of the medical tourism industry, this study aimed to investigate medical tourists’ behavioural intention and satisfaction with social media platforms in Malaysian hospitals by extending the technology acceptance model with context-specific variables. The current study empirically tested the relationship between medical tourists’ perceived usefulness, perceived ease of use, system quality, information quality, perceived risk, self-efficacy, behavioural intention, and satisfaction. To fill the existing gap on the importance of firm-hosted social media platforms online marketing in the decision-making process of medical tourists, and the most significant factors in predicting social media adoption, a model was developed to understand and explain medical tourists’ perception on social media platforms in Malaysian hospitals. Eighteen hypotheses were developed based on prior literature. This study collected and analysed data using a quantitative approach. This study’s data was gathered from 324 medical tourists who visited Malaysia. This study used SmartPLS to examine variable relationships. The findings of structural equation modelling statistically supported fifteen of the study’s eighteen hypotheses. The empirical findings also revealed that all measurement items are critical attributes and valid indicators of the underlying constructs. The current study’s fundamental theoretical contributions include conceptual development by combining and advancing certain aspects of the Technology Acceptance Model (TAM), Social Cognitive Theory (SCT), and Information System Success Model (IS success model), as well as empirical validation of each factor in the proposed model. On the other hand, practitioners in the tourism industries, policymakers, and destination marketers should consider the components of the conceptual framework to fully utilise the social media platform to gain and establish a competitive advantage over industry rivals by providing a better understanding of patients’ demands and barriers to using web-based health information. A low response rate, a limited number of investigated factors, and the risk of positively skewed results could limit the study’s findings. Additional research is necessary to validate the study’s findings and expand its scope.